Liberdade sob tensão: negros e relações interpessoais na São Carlos pós-abolição - Palma, Rogério da (Universidade Federal de São Carlos, 2014)
Post-abolition can be conceptualized as a historical moment in which places and social hierarchies built during centuries crumble. Master and slave, essential categories to understand slaveholding societies, don´t make sense anymore in this new social reality. By bringing the promise of freedom for the former captive, abolition established new bases for negotiation and therefore potentiate certain types of conflicts. While some tried to keep, even if under other terms, the old social asymmetries, former slaves sought to assert their new legal and social status of citizen. Through an approach of a variety of documentary sources of the period, this paper aims to demonstrate that interpersonal relationships were a set of interactions in which these political struggles by redefining certain social situations were present. Through of the interpersonal relationships, one can perceive the establishment of new forms of subjection to the black population, which saw their citizenship be precarious by the racialization of social relations characteristic of this time.
Keywords: Negros; Escravidão - pós-abolição; Relações humanas; Liberdade; São Carlos (SP); Blacks; Post-abolition; Interpersonal relationships; Freedom; São Carlos; CIENCIAS HUMANAS::SOCIOLOGIA